Can the Obesity Crisis Be Reversed? - Ahima, Rexford S. (Book collections on Project MUSE., 2021)
"This book is a readable and scientifically informed primer on obesity and the current obesity crisis. The author is an endocrinologist who works in both the lab and the clinic studying the physiological mechanisms behind diabetes and obesity. This book looks at the science behind weight gain and loss and, informed by the author's clinical work, discusses a variety of treatment options"--